Microsoft PowerPoint 2010 bible - Wempen, Faithe (Indianapolis, Ind. : Wiley Pub., 2010)
"Get the very most out of all that PowerPoint 2010 has to offer while also learning priceless tips and techniques for making good presentations in this new PowerPoint 2010 Bible. Well-known PowerPoint expert and author Faithe Wempen provides formatting tips; shows you how to work with drawings, tables, and SmartArt; introduces new collaboration tools; walks you through five special presentation labs; and more"--Resource description page.
A first look at PowerPoint -- What makes a great presentation? -- Creating and saving presentation files -- Creating slides and text boxes -- Working with layouts, themes, and masters -- Formatting text -- Formatting paragraphs and text boxes -- Correcting and improving text -- Creating and formatting tables -- Drawing and formatting objects -- Creating SmartArt diagrams -- Using and organizing clip art -- Working with photographic images -- Working with charts -- Incorporating content from other programs -- Adding sound effects, music, and soundtracks -- Incorporating motion video -- Creating animation effects and transitions -- Creating support materials -- Preparing for a live presentation -- Designing user-interactive or self-running presentations -- Preparing a presentation for mass distribution -- Sharing and collaborating -- Customizing PowerPoint -- Presenting content without bulleted lists -- Adding sound and movement to a presentation -- Creating a menu-based navigation system -- Creating a classroom game.
Print version record.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Microsoft PowerPoint (Computer file); Microsoft PowerPoint (Computer file); Microsoft PowerPoint (Computer file); Presentation graphics software; COMPUTERS -- Desktop Applications -- Presentation Software; Presentation graphics software